1985
DOI: 10.1021/jo00216a016
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic photodehydroxylation of 9-phenylxanthen-9-ol. Observation of carbocation fluorescence in neutral aqueous solution

Abstract: presence of a trace of dodecahydrotriphenylene ( 20). An authentic sample of 20 was available for comparison.Acknowledgment. This work was supported by the Deutsche Forschungsgemeinschaft and the Fonds der Chemischen Industrie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 2 publications
2
27
1
Order By: Relevance
“…We were really surprised how a strongly absorbing species like this one could be missed by others, particularly when taken into consideration the large number of investigations made on PX+. [7][8][9][10][11][12][13]15,23 We carried out several control experiments to establish that this transient species is indeed a real one and not due to any impurities in the salt or in the solvents used in the experiments. Moreover, we generated PX+ from an acetonitrile solution of PX by adding trifluoroacetic acid (the way earlier studies were conducted) and confirmed that the transient absorption behaviour of the resulting solution is also very similar to that observed with the salt solution.…”
Section: Transient Behaviourmentioning
confidence: 99%
See 3 more Smart Citations
“…We were really surprised how a strongly absorbing species like this one could be missed by others, particularly when taken into consideration the large number of investigations made on PX+. [7][8][9][10][11][12][13]15,23 We carried out several control experiments to establish that this transient species is indeed a real one and not due to any impurities in the salt or in the solvents used in the experiments. Moreover, we generated PX+ from an acetonitrile solution of PX by adding trifluoroacetic acid (the way earlier studies were conducted) and confirmed that the transient absorption behaviour of the resulting solution is also very similar to that observed with the salt solution.…”
Section: Transient Behaviourmentioning
confidence: 99%
“…1-6 9-Phenylxanthenium cation (PX+) is a highly fluorescent and fairly stable species, whose photophysical properties have received noticeable attention. 7-13 PX+ can be generated from 9-phenylxanthenol (PX) in acidic environment pK Rþ ¼ 1I0 AE 0I5 for PX in water ð Þ (scheme 1) 8,14,15 or by photoexcitation of PX in polar (hydroxylic) solvent, where it undergoes adiabatic dehydroxylation in the excited-state surface. 9,10, 15 Wan et al have shown that in the pH range of 3-12 water acts as a catalyst in this photo-induced reaction and the quantum yield of formation of PX+ is 0·4 in 1:1 acetonitrile/water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, recent studies by McClelland et al (2)(3)(4)(5)(6) have utilized these types of reactions for photogenerating carbocation intermediates for study by flash photolysis, from which new insights into structure-reactivity of the photogenerated carbocations in aqueous solutions have been obtained. We have been exploring structure-reactivity effects of the initial photochemical step for a number of systems (7)(8)(9)(10)(11) and have discovered that 9-fluorenols 1 are particularly prone to photosolvolyze (10,11). It has been proposed (10,11) that the reaction proceeds from the singlet state via primary benzylic C-OH bond heterolysis (photodehydroxylation), to generate a 9-fluorenylium ion intermediate, which is rapidly trapped by nucleophiles in the system.…”
mentioning
confidence: 99%